Responses of soil microbial communities to freeze–thaw cycles in a Chinese temperate forest - Sang, Changpeng; Xia, Zongwei; Sun, Lifei; Sun, Hao; Jiang, Ping; Wang, Chao; Bai, Edith (Ecological processes, 2021)
Background Freeze–thaw events are common in boreal and temperate forest ecosystems and are increasingly influenced by climate warming. Soil microorganisms play an important role in maintaining ecosystem stability, but their responses to freeze–thaw cycles (FTCs) are poorly understood. We conducted a field freeze–thaw experiment in a natural Korean pine and broadleaf mixed forest in the Changbai Mountain Nature Reserve, China, to determine the dynamic responses of soil microbial communities to FTCs. Results Bacteria were more sensitive than fungi to FTCs. Fungal biomass, diversity and community composition were not significantly affected by freeze–thaw regardless of the stage. Moderate initial freeze–thaw resulted in increased bacterial biomass, diversity, and copiotrophic taxa abundance. Subsequent FTCs reduced the bacterial biomass and diversity. Compared with the initial FTC, subsequent FTCs exerted an opposite effect on the direction of change in the composition and function of the bacterial community. Soil water content, dissolved organic carbon, ammonium nitrogen, and total dissolved phosphorus were important factors determining bacterial community diversity and composition during FTCs. Moreover, the functional potentials of the microbial community involved in C and N cycling were also affected by FTCs. Conclusions Different stages of FTCs have different ecological effects on the soil environment and microbial activities. Soil FTCs changed the soil nutrients and water availability and then mainly influenced bacterial community composition, diversity, and functional potentials, which may disturb C and N states in this temperate forest soil. This study also improves our understanding of microbial communities regulating their ecological functions in response to climate change.